2019
DOI: 10.1002/cjce.23563
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modelling and predictive control for the sequential collaborative reactors of cobalt removal process under time‐varying conditions

Abstract: The accuracy of the process model directly affects the performance of the model‐based controller. In zinc hydrometallurgy, the overall dynamics of the cobalt removal process can hardly be described by a fixed model since there are a series of interconnected reactors working together under time‐varying inlet and reaction conditions. In this study, an interacting continuously stirred tank reactors (ICSTR) model is developed to describe the cooperative relationship of these cascaded reactors. Considering the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
(49 reference statements)
0
9
0
1
Order By: Relevance
“…Actually, the four reactors interact, and the cobalt removal process can be regarded as a system with multiple interacting CSTR models; thus, it is necessary to study the synergistic relationships among the four reactors. In a specific time interval, the mass of zinc powder in reactor i can be calculated according to Equation (8) [27] :…”
Section: Scstr Model Of Cobalt Removal Processmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually, the four reactors interact, and the cobalt removal process can be regarded as a system with multiple interacting CSTR models; thus, it is necessary to study the synergistic relationships among the four reactors. In a specific time interval, the mass of zinc powder in reactor i can be calculated according to Equation (8) [27] :…”
Section: Scstr Model Of Cobalt Removal Processmentioning
confidence: 99%
“…orp , e eq,j , R, T c , l 1 , l 2 , l 3 , l 4 , and the parameters to be estimated are θ 2 ¼ ½f i j , E e , γ i j , p i j , q i j , χ i , δ, η i . Sun et al [10] estimated the values of f i j , E e , γ i j , p i j , and q i j , and Wang et al [27] reported δ and η i to be 2.9% and 1%, respectively. Therefore, the remaining unknown parameters are the mass-reaction surface coefficients χ i .…”
Section: Parameter Estimation Based On the Augmented State Equation A...mentioning
confidence: 99%
See 2 more Smart Citations
“…A isoterma de Langmuir nesse caso mostrou um processo reversível, onde os processos de adsorção e dessorção pode ser controlada pela concentração hidrogeniônica empregada no meio reacional. Democrática do Congo, onde nunca houve uma transição pacífica de poder e o trabalho infantil ainda é usado em partes do setor de mineração [5][6][7] .…”
Section: Dedicatóriaunclassified